Infographic. Effectiveness of multicomponent lower extremity injury prevention programmes in team-sport athletes: an umbrella review - Valenzuela, P. L.; Brunner, R.; Castillo-Garcia, A.; Friesenbichler, B.; Casartelli, N. C.; Morales, J. S.; Maffiuletti, N. A.; Bizzini, M.; Niedermann, K. (British Journal of Sports Medicine, 2020)
There were overall 11 combinations of exercise elements that were effective in reducing lower extremity injury incidences/rates. Strength and balance exercises were included in 10 programmes, while agility, stretching and warm-up exercises were present in seven effective injury prevention programmes. Plyometrics or technique exercises (eg, lower limb control while landing from a jump) were just present in =5 effective prevention programmes. Interestingly, no combination of exercise elements was found to be effective for the prevention of groin injuries.